2009
DOI: 10.1227/01.neu.0000337064.57270.f0
|View full text |Cite
|
Sign up to set email alerts
|

Intradural Clival Chordoma and Ecchordosis Physaliphora

Abstract: OBJECTIVE Purely intradural clival chordomas are rare neoplasms, and only a few cases have been reported. The reported cases present features similar to ecchordosis physaliphora, which is a notochordal remnant. We describe these 2 entities and their differential diagnoses, clinical courses, and management. This is the first reported case to be treated using a neuroendoscopic technique. CLINICAL PRESENTATION A 60-year-old man … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…EPs are typically found in the prepontine cistern, attached to the dorsal clivus with a small pedicle [ 13 , 25 ]. Other distinctive features are that EPs generally occur in younger people compared to intradural chordomas and that EPs show no enhancement after gadolinium administration on MR imaging, whereas intradural chordomas show a variable enhancement [ 7 , 17 ]. Although differentiating between symptomatic EPs and intradural chordomas based on histology is difficult and debated, Yamaguchi et al [ 26 ] suggested some histological differentiating features.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EPs are typically found in the prepontine cistern, attached to the dorsal clivus with a small pedicle [ 13 , 25 ]. Other distinctive features are that EPs generally occur in younger people compared to intradural chordomas and that EPs show no enhancement after gadolinium administration on MR imaging, whereas intradural chordomas show a variable enhancement [ 7 , 17 ]. Although differentiating between symptomatic EPs and intradural chordomas based on histology is difficult and debated, Yamaguchi et al [ 26 ] suggested some histological differentiating features.…”
Section: Discussionmentioning
confidence: 99%
“…Although differentiating between symptomatic EPs and intradural chordomas based on histology is difficult and debated, Yamaguchi et al [ 26 ] suggested some histological differentiating features. Symptomatic EPs and intradural chordomas tend to show a similar benign behaviour with a very low risk of tumour recurrence after surgical resection [ 7 ]. Chang et al [ 5 ] suggest that EPs and intradural chordomas exist in a continuum from benign hamartomas to aggressive typical chordomas.…”
Section: Discussionmentioning
confidence: 99%
“…reported similar approach by ETSS in the case of intradural chordoma. [5] By ETSS, the surgeon can approach a retroclival prepontine lesion without retracting the brain. To expose the mass, the clivus must be opened, which is a minimally invasive approach.…”
Section: Discussionmentioning
confidence: 99%
“…Interventions of intradural chordomas should be aimed at total removal of the tumor, which may require adjuvant radiotherapy for the residual tissue. [45] Using MRI, Mehnert et al . reported differential diagnoses between EP and a chordoma and found that all EP cases showed no contrast enhancement by gadolinium-enhanced T1-weighted MRI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation